Nanomaterials in hair care and treatment - Pereira-Silva, Miguel (2022)
Hair care and treatment has evolved significantly through the years as new formulations are continuously being explored in an attempt to meet the demand in cosmetic and medicinal fields. While standard hair care procedures include hair washing, aimed at hair cleansing and maintenance, as well as hair dyeing and bleaching formulations for hair embellishment, modern hair treatments are mainly focused on circumventing hair loss conditions, strengthening hair follicle properties and treat hair infestations. In this regard, active compounds (ACs) included in hair cosmetic formulations include a vast array of hair cleansing and hair dye molecules, and typical hair treatments include anti-hair loss ACs (e.g. minoxidil and finasteride) and anti-lice ACs (e.g. permethrin). However, several challenges still persist, as conventional AC formulations exhibit sub-optimal performance and some may present toxicity issues, calling for an improved design of formulations regarding both efficacy and safety. More recently, nano-based strategies encompassing nanomaterials have emerged as promising tailored approaches to improve the performance of ACs incorporated into hair cosmetics and treatment formulations. The interest in using these nanomaterials is based on account of their ability to: (1) increase stability, safety and biocompatibility of ACs; (2) maximize hair affinity, contact and retention, acting as versatile biointerfaces; (3) enable the controlled release of ACs in both hair and scalp, serving as prolonged AC reservoirs; besides offering (4) hair follicle targeting features attending to the possibility of surface tunability. This review covers the breakthrough of nanomaterials for hair cosmetics and hair treatment, focusing on organic nanomaterials (polymer-based and lipid-based nanoparticles) and inorganic nanomaterials (nanosheets, nanotubes and inorganic nanoparticles), as well as their applications, highlighting their potential as innovative multifunctional nanomaterials towards maximized hair care and treatment. Statement of significance This manuscript is focused on reviewing the nanotechnological strategies investigated for hair care and treatment so far. While conventional formulations exhibit sub-optimal performance and some may present toxicity issues, the selection of improved and suitable nanodelivery systems is of utmost relevance to ensure a proper active ingredient release in both hair and scalp, maximize hair affinity, contact and retention, and provide hair follicle targeting features, warranting stability, efficacy and safety. This innovative manuscript highlights the advantages of nanotechnology-based approaches, particularly as tunable and versatile biointerfaces, and their applications as innovative multifunctional nanomaterials towards maximized hair care and treatment.